Kesulitan Peserta Didik dalam Berinteraksi dengan Pendidik saat Pembelajaran di Sekolah - Olyvia Hera Anggreana; Nafisa Amelia; Bintang Oktaviana; Tita Nur Anggraini; Sri Suwartini (Jurnal Pendidikan, Sains Dan Teknologi, 2025)
This article discusses the various difficulties students experience when interacting with teachers during the learning process at school. The relationship between teachers and students is crucial because it significantly impacts learning success. A lack of communication and openness often makes it difficult for students to understand lessons and lowers their enthusiasm for learning. The purpose of this paper is to explain the causes of interaction barriers, their impact on learning outcomes, and how teachers can address them. The study revealed that interaction barriers can arise from internal factors such as a lack of interest and self-confidence, as well as external factors such as an unsupportive learning environment and unengaging teaching methods. To overcome these challenges, teachers need to create an active learning atmosphere, use a variety of teaching methods, and provide ongoing guidance and encouragement. A good relationship between teachers and students can make the learning process more effective and foster students' social and emotional development.